Notes to Philosophy 167: Class 5 -- Other Developments in Astronomy from 1609 to 1642 -- Part 1. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Introduction: Galileo's Place in 17th Century Science -- Galileo Galilei: A Biographical Sketch; Generally corresponds to the video segment: Class 5, Part 1.